Efektifitas Trainer Pneumatik sebagai Media Pembelajaran pada Materi Pengontrolan Gerak Sekuensial - Purnawan, Purnawan (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
The purpose of this study is to determine the effectiveness of pneumatic trainer as instructional media in sequential motion control material. The research uses quasi-experimental method with pre and post test design. The material is limited to sequential motion control using two actuators for objects transfer. Control class uses instructional media training kit, while experimental class uses development-result trainer. Essay tests are in form of diagram circuit for application of electroplating products transfer. The results show that the developed pneumatic trainer and training kit are quite effective as media of learning in sequential motion control. Statistical tests indicate no significant difference between the two groups, so that it can be concluded that compared to training kit, the developed pneumatic trainer is not more effective as learning media.